Pharmacology in intensive care patients: the role of renal clearance in antibiotic dosing - Mat Nor, Mohd Basri; Abdul Rahim, Shahir Asraf (Malaysian Society of Anaesthesiologists, 2019)
Sepsis, a dysregulated host response to infection is common in the intensive care unit (ICU) worldwide. It remains a major challenge for critical care physicians because of the associated high mortality and morbidity. According to Malaysian Registry of Intensive Care (MRIC) Report in 2017, sepsis was the first leading cause of admission to the Ministry of Health ICUs with mortality rate of 52.8%.1 In management of critically ill patients with sepsis and septic shock, there is compelling evidence that source control of the pathogen, early and appropriate administration of antimicrobial therapy remain the most important intervention. To achieve favourable outcomes, the goal is to achieve effective drug concentrations at the site of infection. In critically ill patients, development of organ failure may complicate antibiotic dosing. Two pharmacokinetic parameters that vary with greatest significance in patients with MODS are Vd and drug CL. In presence of AKI, antibiotic dose adjustments in patients with reduced clearance are commonly applied to avoid adverse effects. Augmented renal clearance is another important phenomenon which is a manifestation of enhanced renal function. Early recognition of patients at risk of ARC allows further intervention to prevent antibiotic failure. In patients with ARC, higher doses of renal eliminated antibiotics are recommended or administration of non-renally eliminated drugs should be considered.